2021
DOI: 10.1055/s-0041-1736531
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Arteriovenous Fistula Creation: A Review

Abstract: Endovascular arteriovenous fistula (endoAVF) creation offers a minimally invasive method for the formation of arteriovenous shunts utilized for hemodialysis. Currently, there exist two similar yet unique devices: WavelinQ and Ellipsys. This review analyzes the anatomy, pre- and postoperative considerations, fistula creation methods, and outcomes associated with endoAVF. Currently, data are limited with regard to clinical efficacy of endoAVFs when compared to surgical AVFs. However, early data suggest endoAVFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
1
0
7
Order By: Relevance
“…La vena perforante comunica el sistema venoso superficial y profundo y, en la mayoría de los casos, se ubica en la zona distal del codo. La presencia y características de esta vena son importantes para la creación de una FAV percutánea, ya que es la que permite que la sangre venosa arterializada del sistema venoso profundo llegue al sistema venoso superficial y la FAV pueda utilizarse 11 .…”
Section: Valoración Preoperatoriaunclassified
See 3 more Smart Citations
“…La vena perforante comunica el sistema venoso superficial y profundo y, en la mayoría de los casos, se ubica en la zona distal del codo. La presencia y características de esta vena son importantes para la creación de una FAV percutánea, ya que es la que permite que la sangre venosa arterializada del sistema venoso profundo llegue al sistema venoso superficial y la FAV pueda utilizarse 11 .…”
Section: Valoración Preoperatoriaunclassified
“…La profilaxis antibiótica se alinea con los protocolos hospitalarios de cada centro 7 . En cuanto a la anestesia, es posible realizar un bloqueo regional axilar o supraclavicular para favorecer la dilatación venosa 7 , aunque la anestesia local junto con sedación también es una opción viable 11 .…”
Section: Procedimiento Quirúrgicounclassified
See 2 more Smart Citations
“…Health care providers create AVFs either through open surgical or minimally invasive endovascular or percutaneous procedures (i.e., endovascular AVF creation [EndoAVF]). 13,14 Open surgical procedures involve a vascular surgeon creating an incision in an upper extremity to create an AVF, typically using nonabsorbable sutures� 13,14 EndoAVF, a newer approach, involves a health care provider accessing blood vessels through punctures in the skin and guiding an endovascular device to a site where it can be used to create an AVF, either through radiofrequency or thermal energy� 13 Whether performed surgically or endovascularly, procedures to create AVFs ideally should take place 3 to 6 months before a patient needs hemodialysis to allow time for any necessary surgical revision and for the site to mature so it can be accessed using a needle for hemodialysis� 5,13 However, as detailed by Brown et al�, 15 patients may experience barriers to accessing or benefiting from these procedures. Of note, the authors reported that certain equity-deserving groups, such as older adults, females, and people who are Black, living in rural and remote communities, or without health insurance may experience disproportionately lower rates of timely access to AVFs and successful AVF maturation� 15 Traditional open surgical AVF creation procedures require operating room time� However, resource constraints may result in extended surgical wait times, limiting the number of patients who can initiate hemodialysis with AVF� When unable to receive timely access to a functional AVF, patients may receive a CVL, which, as detailed earlier, may be associated with higher rates of risks such as infections� 6,7 The novel, minimally invasive EndoAVF procedure may reduce costs and wait times associated with surgery� EndoAVF may also be safe, although evidence regarding its clinical efficacy may be limited in quantity and quality.…”
Section: Context and Policy Issuesmentioning
confidence: 99%